Mac bible - Spivey, Dwight; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2009)
"This essential guide answers all your questions on using a Macintosh computer, whether you're unpacking your very first Mac after switching from a PC or upgrading from an older Mac. You'll walk through all pre-installed Mac applications, including using Mac OS X, browsing the Web using Safari, downloading music from the iTunes store, troubleshooting Mac-specific problems, organizing photos in iPhoto, organizing calendars in iCal, editing digital video in iMovie, and more."--Resource description page.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Macintosh (Computer); Mac OS; Macintosh (Computer) -- Maintenance and repair; Macintosh (Computer) -- Handbooks, manuals, etc; Word processing -- Handbooks, manuals, etc; iTunes -- Handbooks, manuals, etc; Internet -- Handbooks, manuals, etc; Electronic mail messages -- Handbooks, manuals, etc; iMovie -- Handbooks, manuals, etc; Electronic books